Plasmonic Nanoparticles for Large-Area, High- Enhancement Surface-Enhanced Raman Scattering Sensors - Madhloom, Ahmed Ayad; Ali, Hussein Abbas (American Journal of Botany and Bioengineering, 2024)
Silicon technology offers almost unlimited possibilities and pervades our day life the main reason in the information technology is to have the possibility of integrating low – dimensional structures showing appropriate optoelectronic properties with well-established and highly advanced silicon microelectronics technology. The structural and morphological properties of electrochemically etched porous silicon are investigated using SEM, The porous silicon layers were formed in 40% HF solution and ethanol of 99% in a ratio of n-type silicon. The surface morphology as characterized by scanning electron microscope reveals that the variation in etching time can produce microscopic roughness on the etched surfaces. The AuNPAs/PS that deposited on porous silicon nano-photonic sensors have been used for performing SERS detections of low concentration of chlorpyrifos pesticide, with concentration 25*10-8 to 3*10-5 M.